History of Historical Statistics of the United States - Carmel Ullman Chiswick (Institute for the Study of Labor (IZA), 2003)
Historical Statistics of the United States is the premier source of quantitative evidence on American economic, social, political, demographic, and institutional history. Introduced in 1949 as a time-series supplement to the Statistical Abstract of the United States, it has inspired similar efforts in countries around the world. At the time of this writing, when the current edition is a quarter-century out of date, Historical Statistics is still a basic reference generating hundreds of citations annually in academic, professional, and journalistic publications. This essay describes the origins of this influential work and how it evolved over time.
Keywords: C8; C1; 330; Historical Statistics; Statistical Abstract; U.S. Census Bureau; time series; quantitative evidence; Statistisches Handbuch; Vereinigte Staaten